English Language Needs of Tahfiz Students in Malaysia - Zahidah Sarkawi; Hazlina Abdullah; Haliza Harun; Nursyuhada' Ab. Wahab; Rahimah Saimin; Myra Aidrin Mohd Ali; Dini Farhana Baharudin (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia